A Single-Batch Fermentation System to Simulate Human Colonic Microbiota for High-Throughput Evaluation of Prebiotics - Takagi, Risa (PLoS One, 2016)
We devised a single-batch fermentation system to simulate human colonic microbiota from fecal samples, enabling the complex mixture of microorganisms to achieve densities of up to 10(11) cells/mL in 24 h. 16S rRNA gene sequence analysis of bacteria grown in the system revealed that representatives of the major phyla, including Bacteroidetes, Firmicutes, and Actinobacteria, as well as overall species diversity, were consistent with those of the original feces. On the earlier stages of fermentation (up to 9 h), trace mixtures of acetate, lactate, and succinate were detectable; on the later stages (after 24 h), larger amounts of acetate accumulated along with some of propionate and butyrate. These patterns were similar to those observed in the original feces. Thus, this system could serve as a simple model to simulate the diversity as well as the metabolism of human colonic microbiota. Supplementation of the system with several prebiotic oligosaccharides (including fructo-, galacto-, isomalto-, and xylo-oligosaccharides; lactulose; and lactosucrose) resulted in an increased population in genus Bifidobacterium, concomitant with significant increases in acetate production. The results suggested that this fermentation system may be useful for in vitro, pre-clinical evaluation of the effects of prebiotics prior to testing in humans.